Makna Merdeka Belajar dan Penguatan Peran Guru di Sekolah Menengah Pertama Negeri 5 Muaro Jambi - Mulyadi, Mulyadi; Helty, Helty; Vahlepi, Sahrizal (Jurnal Ilmiah Dikdaya, 2022)
The essence of independent learning is the freedom of teachers and students in the learning process. This freedom has not been experienced by teachers and students so far because teachers are more involved in the administration of education and learning. Teachers also do not understand the concept and its role in the policy of independent learning. The purpose of this study is to explain the concept and meaning of independent learning, the role of teachers in independent learning. The method used is the library method. Content analysis was used to analyze research data. The results of this study are (1) independent learning includes 4 policies, namely national standard school exams carried out by the school, minimum skills assessment and character surveys, simplification of lesson plans, zoning system for new student admissions; (2) the meaning of independent learning includes freedom of thought, freedom to innovate, independent and creative learning, freedom for happiness; (3) the teacher's role varies widely, including independent learning facilitators, innovative and creative teachers, teachers with characteristics as teachers, and teachers as motivators. Based on this explanation, this study concludes that understanding the meaning of independent learning and the role of teachers in independent learning helps teachers and students be more independent in thinking, more innovative and creative, and happy in learning activities.